(untitled) (Research, Society and Development, 2020)
In this article we aimed to outline the profile of students licenciados from the Mathematics Degree course at Unespar - Campo Mourão, to then share with teachers, other students of the course and future entries, what are their expectations and disappointments as Graduated from university. For this purpose, studies were carried out on the institution’s documents and an analysis in a questionnaire applied to graduates of the Mathematics degree course, from the years 2011 to 2017, we used the methodological content analysis tool. With this we identified that students who participate in programs with PIC and PIBID are potentially active in the area of their training, while students who did not participate in programs are considered as potentially inactive in the area of their training, we intend to enable research and tactics that collaborate for a policy follow-up of these academics, aiming to contribute for future mathematics graduates to choose teaching. With this research we intend to enable research and tactics that collaborate for a policy of monitoring these academics, aiming to contribute for future mathematics graduates to choose teaching. We highlight how important it is for alumni who were able to somehow enjoy other activities at the university other than teaching, be it research projects, extension or teaching projects.